Open Suprascapular Nerve Decompression at the Spinoglenoid Notch - William E. Harkin, M.D.; Benjamin Kerzner, M.D.; John Scanaliato, M.D.; Sydney Garelick, B.S.; Tyler Williams, B.S.; Gregory P. Nicholson, M.D.; Grant E. Garrigues, M.D. (Arthroscopy Techniques, 2024)
Suprascapular nerve (SSN) entrapment is a rare but significant cause of posterior shoulder pain and weakness. Compression of the nerve at the level of the spinoglenoid notch leads to weakness and atrophy of the infraspinatus. A detailed history and physical examination along with appropriate workup are paramount to arrive at this diagnosis. Surgical decompression is indicated in cases refractory to conservative management. In this Technical Note, we describe our technique for open decompression of the SSN at the spinoglenoid notch. This approach permits direct visualization of the SSN and allows for a safe, reliable, and thorough decompression.